Working with Clients with ADHD: Reflections on Secondary Capacities - Anna Jaźwińska-Chren (The Global Psychotherapist)
The purpose of this article is to outline the therapeutic model employed in working with individuals with ADHD, grounded in the principles of PPT. It is based on the five stages of the therapeutic process. An important element is the integration of the concept of secondary capacities into psychoeducation and therapeutic dialogue. This article explores how the concept of secondary capacities – socially reinforced qualities such as punctuality, reliability, and self-control – can both illuminate and complicate the therapeutic process. Drawing on clinical experience and practical strategies, we reflect on the importance of reframing ADHD-related struggles not as moral failings but as tensions between neurological predispositions and cultural expectations. Using the described model in therapeutic work with people with a diagnosis of ADHD facilitates depersonalization of symptoms. It opens a space for changing the narrative about the self from a perspective of compassion rather than guilt. With this perspective, therapy becomes not only a space for coping with symptoms but also for identity reconstruction, self-compassion, and meaningful personal growth.